Watercraft-related drownings among New York State residents, 1988-1994. - Browne, Marilyn L. (Association of Schools of Public Health, 2003)
OBJECTIVE: To describe environmental and personal risk factors associated with watercraft-related drownings. This information may be useful in developing boating safety programs, regulations, and enforcement priorities. METHODS: A companion article in this issue (Unintentional Drownings Among New York State Residents, page 448) summarizes an investigation of 883 non-bathtub drownings among New York State residents for the years 1988 to 1994 using medical examiner, coroner, police, and hospital records in addition to death certificate data. This report details the environmental and personal risk factors associated with 216 watercraft-related drownings. RESULTS: Ninety-three percent of watercraft-related drowning victims were male, with the highest rate of drowning observed among males ages 15-44 years. Most commonly, the victim entered the water when the watercraft capsized (36%), the victim fell overboard (24%), or the victim intended to swim (11%). Personal flotation devices (PFDs) were known to be worn by only 9% of drowning victims, and in these cases other risks overwhelmed the effectiveness of the PFD. Of 73 individuals 15 years of age or older for whom adequate blood alcohol concentration analyses were provided, 44% were positive for blood alcohol. CONCLUSIONS: Based on this study, increased use of PFDs, avoidance of dangerous currents, and less alcohol use by operators and passengers of all types of watercraft would result in a reduction in watercraft-related drownings. In addition to continued education efforts, boating safety measures that deserve consideration include enforcement of current PFD and boating while intoxicated (BWI) regulations and expansion of BWI laws to apply to all boaters.